PENGOLAHAN BAHAN PUSTAKA DI PERPUSTAKAAN FAKULTAS ILMU SOSIAL DAN ILMU POLITIK (FISIP) UNIVERSITAS TANJUNGPURA - Putri Pratiwi; Sahidi Sahidi (Universitas Tanjungpura, 2021)
AbstractThis research was motivated by the curiosity of research in knowing the processof processing library materials at the library of the Faculty of Social andPolitical Sciences (Fisip) of Tanjunpura University. This type of recearch witha qualitative approach. Sources of data in this study were the head of the libraryand the Fisip library staf totalin 3 people to be interviewed. Data collectiontechniques through observation, interviews, dokumentation. Data analysistechniques in the form of data reduction, data presentation, and drawingconclusions to obtain the final result. The result of the study indicate that theprocessing of library materials has not met the processing prosedures due to theclassification numbering process that uses onesearch compared to DDC. Theprocessing process starts from copmleteness as well as arranging books onshelves (selving). Constraints faced by the lack of a sense of respinsibility inprocessing and the large number of collections that exceed the number of shelverin the Fisip library.Keywords : processing library materials, library.